INFLUENCE OF SOCIAL NORMS AND SPIRITUAL TENDENCIES TO MORAL CONSIDERATIONS IN RELIGIOUS SCHOOL STUDENTS - Yusoff, Mohd Zailani Mohd; Othman, Mohamad Khairi (Ar Raniry : International Journal of Islamic Studies, 2017)
The main purpose of this study is to trace information related to the influence of social norms and spiritual tendencies to moral considerations in religious school students. This study aims to identify the influence of the dimensions of Islamic spiritual tendencies and the dimension of social customs to moral considerations based on established schemes. Three measuring tools were used in this study, namely Ujian Skema taakulan Akhlak (UPSTA), Kuesioner Kecenderungan Kerohanian Islam (ISDQ) dan Tes Sikap dan Pegangan Terhadap Standar Prevalensi Sosial (USPSK). The subjects of the study consisted of 500 students who were divided into gender according to the type of religious high school in the state of Kelantan which were randomly selected from Sekolah Menengah Kebangsaan Agama (SMKA), Maahad Muhammadi (MM), Maahad Tahfiz Al-Quran / Sains (MTAQ / MTS), Sekolah Agama Rakyat (SAR) dan Sekolah Agama Swasta (SAS). This review review uses a quantitative method based on cross-sectional research approach (Cross Sectional). Data were collected from the above three tests and analyzed by using statistical analysis of stepwise multiple regression at significant degree p <0.05. The results of the study show that dimensions of faith and faith play a powerful role in the moral consideration of high school religious students. The findings also show the dimensions of faith, intrinsic dimensions and extrinsic dimensions in the aspect of Islamic spiritual tendency to have significant influence (R² = .465, sig.) On the moral considerations of religious school students. However, the dimensions of human rights within social norms varied only (R² = .017, sig .003) on moral considerations among religious school students in Kelantan. This review provides a fresh understanding of the moral issues of religious secondary school students. The tendency of religious school students on Islamic spiritual aspects plays an important role in determining the quality of their moral considerations.